Drug Cravings and Its Relationship With Family Communication Patterns and Resiliency Through the Mediatory Role of Difficulty in Cognitive Emotion Regulation - Ali Badie; Behnam Makvandi; Saeed Bakhtiarpour; Reza Pasha (Iran University of Medical Sciences, 2020)
Background: Clients visiting Methadone Maintenance Treatment (MMT) clinics frequently face relapse during treatment. The present study was done to investigate the relationship between family communication patterns and resiliency and craving for drugs through the mediatory role of difficulty in cognitive emotion regulation among clients treated with methadone. Methods: This descriptive correlational study was done on 213 drug addicts who referred to Ahvaz methadone treatment clinics in 2019, selected using convenience sampling. The research instruments included the Revised Family Communication Patterns (RFCP), the Connor-Davidson Resilience Scale (CD-RISC), the Cognitive Emotion Regulation Questionnaire (CERQ), and Craving Beliefs Questionnaire (CBQ). The proposed model was evaluated by path analysis using AMOS software. Results: The results revealed a significant negative relationship between family communication patterns and the craving for drugs (P<0.01). There was a significant negative relationship between resiliency and craving for drugs in clients treated with methadone (P<0.01). Difficulties in cognitive emotion regulation had a mediating role in the relationship between family communication and resiliency with a craving for drugs (P<0.05). Conclusion: According to the results of this study, the proposed model had a good fit. The family communication patterns as the external and environmental factors, and resiliency as an internal and psychological factor, affect control over negative emotions and craving for drugs. Therefore, they must be considered by therapists to keep the client in the process of treatment.